Herpes Simplex Virus Encephalitis With Initial Negative Polymerase Chain Reaction in the Cerebrospinal Fluid: Prevalence, Associated Factors, and Clinical Impact*. Issue 7 (3rd February 2022) - de Montmollin, Etienne; Dupuis, Claire; Jaquet, Pierre; Sarton, Benjamine; Sazio, Charline; Susset, Vincent; Conrad, Marie; Argaud, Laurent; Demeret, Sophie; Tadié, Jean Marc; Barbier, François; Wolff, Michel; et al.
Abstract : OBJECTIVES: To describe the prevalence, associated factors, and clinical impact of an initial negative herpes simplex virus (HSV) polymerase chain reaction (PCR) in critically ill patients with PCR-proven HSV encephalitis. DESIGN: Retrospective multicenter study from 2007 to 2017. SETTING: Forty-seven French ICUs. PATIENTS: Critically ill patients admitted to the ICU with possible/probable acute encephalitis and a positive cerebrospinal fluid (CSF) PCR for HSV. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We included 273 patients with a median Glasgow Coma Scale score of 9 (6–12) at ICU admission. CSF HSV PCR was negative in 11 cases (4%), exclusively in lumbar punctures (LPs) performed less than 4 days after symptoms onset. Patients with an initial negative PCR presented with more frequent focal neurologic signs (4/11 [36.4%] vs 35/256 [13.7%]; p = 0.04) and lower CSF leukocytosis (4 cells/mm 3 [3–25 cells/mm 3 ] vs 52 cells/mm 3 [12–160 cells/mm 3 ]; p < 0.01). An initial negative PCR was associated with an increased delay between LP and acyclovir treatment (3 d [2–7 ] vs 0 d [0–0 d]; p < 0.01) and was independently associated with a poor neurologic outcome at hospital discharge (modified Rankin Scale score ≥ 4) (adjusted odds ratio, 9.89; 95% CI, 1.18–82.78). CONCLUSIONS: In severe herpes simplex encephalitis, initial negative CSF HSV PCR occurred in 4% of cases and was independently associated with worse neurologic outcome at hospital discharge. In these patients, a systematic multimodal diagnostic approach including early brain MRI and EEG will help clinicians avoid delayed acyclovir initiation or early inappropriate discontinuation.